ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL (STUDI KASUS PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI PERIODE 2012 â€“ 2016) - Guna, Michael Adi; Sampurno, R. Djoko (Diponegoro Journal of Management, 2018)
Capital Structure or in English called debt to equity ratio is one financial ratio that compares the total debt to capital. Capital Structure has a usefulness that is to be a management reference of a company in making decisions about working capital to be used by companies, that the capital itself was funded by external / debt and capital funded by internal company. This research was conducted on companies engaged in food and beverage. This study also looks deeper about the relationship between capital structure with profitability, asset structure, firm size, sales growth and current ratio.The method used is multiple regression analysis with classical assumption test as statistical requirement. The data used in this study consisted of annual data from the related Â company financial statements in the period 2012-2016. The sample is divided according to the purpose of research is on 14 food and beverage companies.The results showed that simultaneously the character of profitability, asset structure, current ratio, firm size and sales growth influenced the performance of capital structure by 43.3%. In partial test of capital structure. Profitablility, company size, asset structure and sales growth have positive and insignificant effect on capital structure performance. While the current ratio has a positive and significant effect on the performance of capital structure.